Complete genome sequence of Candidatus Ruthia magnifica. Issue 2 (September 2010) - Roeselers, Guus; Newton, Irene; Woyke, Tanja; Auchtung, Thomas; Dilly, Geoffrey; Dutton, Rachel; Fisher, Meredith; Fontanez, Kristina; Lau, Evan; Stewart, Frank; Richardson, Paul; Barry, Kerrie; et al.
Abstract The hydrothermal vent clamCalyptogena magnifica (Bivalvia :Mollusca ) is a member of theVesicomyidae . Species within this family form symbioses with chemosyntheticGammaproteobacteria . They exist in environments such as hydrothermal vents and cold seeps and have a rudimentary gut and feeding groove, indicating a large dependence on their endosymbionts for nutrition. TheC. magnifica symbiont, Candidatus Ruthia magnifica, was the first intracellular sulfur-oxidizing endosymbiont to have its genome sequenced (Newtonet al. 2007). Here we expand upon the original report and provide additional details complying with the emerging MIGS/MIMS standards. The complete genome exposed the genetic blueprint of the metabolic capabilities of the symbiont. Genes which were predicted to encode the proteins required for all the metabolic pathways typical of free-living chemoautotrophs were detected in the symbiont genome. These include major pathways including carbon fixation, sulfur oxidation, nitrogen assimilation, as well as amino acid and cofactor/vitamin biosynthesis. This genome sequence is invaluable in the study of these enigmatic associations and provides insights into the origin and evolution of autotrophic endosymbiosis.